Revisoría fiscal y control fiscal como formas de control estatal en Colombia (2013)
The phenomenon of corruption is a scourge that has affected the democratic structures of different states. Consequently, they have adopted control schemes to mitigate the devastating effects of this social phenomenon. Fiscal control emerges as the most important link in the chain of custody of the State resources. The aim of this paper is to analyze the influence of statutory auditing in the exercise of state fiscal control in Colombia, under the provisions of the Constitution of Colombia, the Commercial Code (Act 410 of 1971) and Law 42 of 1993. A non-experimental research was applied using a qualitative and bibliographic approach. The method was inductive and consisted in the documentary analysis of 47 auditing reports conducted in state enterprises (national and provincial) and 47 reports issued by auditors of companies that manage public resources. It was found that the fiscal control exercised by public officials and the functions performed by auditors of organizations that manage state resources are incompatible, so auditing has not exerted positive influence in a more efficient fiscal control, and consequently it has failed to ostensibly alleviate corruption. For this reason it is desirable that institutions where these two kinds of state control concur, strategies should be established in terms of sharing information and procedures and especially to use the findings of public auditors as relevant information in order to further the control upon public resources.